Caracterização genética de seis plantéis de tilápia (Oreochromis) utilizando marcadores microssatélites - Daniela Chemim de Melo (2004)
In the present study, six commercial stocks of tilapias (Ceará, Chitralada, Israel, Nilótica, Taiwan and Red) of the southeast region of the country were genetically characterized using five microsatelittes loci. A total of 235 individuals were analyzed. The results showed a great genetic difference among them obtained by the allele fixation index (Fst=0,3263), and that considerable loss of heterozigosity is occurring in almost all the stocks, according to the estimate inbreeding coefficient (Fis=0,0486). The stocks Israel and Nilótica were the most genetically similar (Ig=0,6663), while Chitralada and Taiwan stocks were the ones that presented less genes in common (Ig=0,2463). The stock denominated Red was the most distinct among all of them. Regarding the origin of the stocks the results showed by the dendrogram indicated that there is some contradictions between the data obtained from the literature about the stocks origin records.